2016
DOI: 10.1111/jop.12527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV infection in the micronuclei frequency on the oral mucosa

Abstract: HIV patients under HAART therapy and low viral load values showed higher frequency of multiple MNs, which, although not statistically significant, may be caused by the action of the Vpr gene, an accessory gene of HIV. These results corroborate the theory of HIV infection cytogenetic damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Our findings are in line with those of Lima and colleagues that show an increase in the frequency of multiple MN in oral mucosa cells in HIV patients compared to healthy controls [35]. …”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in line with those of Lima and colleagues that show an increase in the frequency of multiple MN in oral mucosa cells in HIV patients compared to healthy controls [35]. …”
Section: Discussionsupporting
confidence: 93%
“…In 2013, Olivero et al 24 observed that the use of ART, with reverse transcriptase inhibitor drugs (zidovudine, lamivudine, abacavir, and nevirapine) in the offspring of pregnant monkeys not carrying HIV, which were medicated during pregnancy and after birth, revealed genomic instability and mutagenic effects that persisted for 3 years (final year of research). Moraes Filho et al 25 evaluated that cytotoxicity and genotoxicity of different concentrations of ART composed of tenofovir, lamivudine, and zidovudine, lamivudine, and efavirenz, in mice, through the comet assay and bone marrow micronucleus test. The increase of MN in buccal mucosal cells was observed by Lima et al 26 , in adults with HIV using ART, with low viral load.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Lima et al [ 32 ] investigated micronuclei in exfoliated oral cells of HIV-infected individuals undergoing ART and non-infected controls ( n = 30 each group). In addition to measuring MN frequency, the authors separated micronuclei into two categories: (I) single MN and (II) multiple micronuclei.…”
Section: Impacts Of Hiv Infection and Treatment On Chromosomal Integr...mentioning
confidence: 99%
“…Considering the two MN categories mentioned, a statistically significant increased mean of single MN in the cells of the controls compared to those of HIV-infected individuals and a non-significant increase in the occurrence of multiple micronuclei in the cells of the HIV group compared to the controls were reported. However, the small sample size of this study and the absence of difference in overall MN frequency between the groups may limit interpretations of these findings [ 32 ].…”
Section: Impacts Of Hiv Infection and Treatment On Chromosomal Integr...mentioning
confidence: 99%